2020
DOI: 10.1038/s41598-020-72338-3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in small arteries and early signs  of atherosclerosis in ApoE knockout rats

Abstract: Endothelial dysfunction is recognized as a major contributor to atherosclerosis and has been suggested to be evident far before plaque formation. Endothelial dysfunction in small resistance arteries has been suggested to initiate long before changes in conduit arteries. In this study, we address early changes in endothelial function of atherosclerosis prone rats. Male ApoE knockout (KO) rats (11- to 13-weeks-old) were subjected to either a Western or standard diet. The diet intervention continued for a period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
2
25
1
Order By: Relevance
“…This might also be the case at the basal endothelial activity state in our rats. A previous study on ApoE KO rats also showed changes in COX-dependent signaling and increased endothelium-dependent contraction in pulmonary arteries of ApoE KO rats (Berenji Ardestani et al, 2020). In this study, incubation of pulmonary arteries with indomethacin and L-NAME made no difference in neither contractile or relaxation responses between the two groups.…”
Section: Discussionsupporting
confidence: 45%
“…This might also be the case at the basal endothelial activity state in our rats. A previous study on ApoE KO rats also showed changes in COX-dependent signaling and increased endothelium-dependent contraction in pulmonary arteries of ApoE KO rats (Berenji Ardestani et al, 2020). In this study, incubation of pulmonary arteries with indomethacin and L-NAME made no difference in neither contractile or relaxation responses between the two groups.…”
Section: Discussionsupporting
confidence: 45%
“…In this study, incubation of pulmonary arteries with indomethacin and L-NAME made no difference in neither contractile or relaxation responses between the two groups. The difference in the present result, compared to the previous (Berenji Ardestani et al, 2020), could be due to the lower extent of hypercholesteremia in this current study; rats were fed a Western diet for a period of 8 weeks and total plasma cholesterol level was much lower (7.8 mmol/L) compared to the previous study (36.43 mmol/L). Accordingly, it is possible that the extent of oxidative stress was less (Berenji Ardestani et al, 2019).…”
Section: Discussioncontrasting
confidence: 95%
“…Although we believe the last possibility is most probable, a clear answer will await further investigation. A similar result was reported earlier in mesenteric arteries of ApoE KO rats on a Western diet (Berenji Ardestani et al, 2020). ACh-induced responses in the presence of different endothelium-dependent relaxation blockers in mesenteric artery were similar to those found in pulmonary arteries (Supplementary Figures S5, S6), confirming the elevated contribution of NO in endothelium-dependent relaxation in the non-diving group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, Apolipoprotein E knock-out (ApoE KO) animals have emerged as a reliable model to assess the early development of endothelial dysfunction in atherosclerotic disease (Getz and Reardon, 2012;Wei et al, 2015;Rune et al, 2018;Lee et al, 2019). In a previous study, we have shown that male ApoE KO rats develop signs of pro-atherosclerotic changes when fed a high-fat western diet (Berenji Ardestani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%